Current status of urban wastewater treatment plants in China. (July 2016) - Zhang, Q.H.; Yang, W.N.; Ngo, H.H.; Guo, W.S.; Jin, P.K.; Dzakpasu, Mawuli; Yang, S.J.; Wang, Q.; Wang, X.C.; Ao, D.
Abstract: The study reported and analyzed the current state of wastewater treatment plants (WWTPs) in urban China from the perspective of treatment technologies, pollutant removals, operating load and effluent discharge standards. By the end of 2013, 3508 WWTPs have been built in 31 provinces and cities in China with a total treatment capacity of 1.48 × 10 8  m 3 /d. The uneven population distribution between China's east and west regions has resulted in notably different economic development outcomes. The technologies mostly used in WWTPs are AAO and oxidation ditch, which account for over 50% of the existing WWTPs. According to statistics, the efficiencies of COD and NH3 –N removal are good in 656 WWTPs in 70 cities. The overall average COD removal is over 88% with few regional differences. The average removal efficiency of NH3 –N is up to 80%. Large differences exist between the operating loads applied in different WWTPs. The average operating loading rate is approximately 83%, and 52% of WWTPs operate at loadings of < 80%, treating up to 40% of the wastewater generated. The implementation of discharge standards has been low. Approximately 28% of WWTPs that achieved the Grade I-A Discharge Standard of Pollutants for Municipal Wastewater Treatment Plant (GB 18918–2002) were constructed after 2010. The sludge treatment and recycling rates are only 25%, and approximately 15% of wastewater is inefficiently treated. Approximately 60% of WWTPs have capacities of 1 × 10 4  m 3 /d–5 × 10 4  m 3 /d. Relatively high energy consumption is required for small-scale processing, and the utilization rate of recycled wastewater is low. The challenges of WWTPs are discussed with the aim of developing rational criteria and appropriate technologies for water recycling. Suggestions regarding potential technical and administrative measures are provided. Graphical abstract: Highlights: 3508 wastewater treatment plants (WWTPs) were summarized. Population distribution and economic development caused regional difference of WWTPs. Pollutant removal, operating load, discharge standards in 7 regions were presented. Suggestions regarding potential technical and administrative measures were provided.